“This Folktale Comes from Asia through the Wars…” The Soldier – Storyteller in the Lithuanian Village Community in the Second Half of the 19th – the First Half of the 20th Century - Šlekonytė, Jūratė (Tautosakos darbai, 2020)
The article aims at evaluating the historical role of soldiers as storytellers in the Lithuanian folktale tradition, and establishing data regarding such storytelling to have actually taken place, as well as circumstances of acquiring these folklore pieces. The analysis follows two directions. First, the Lithuanian folktales are regarded as a source of information about the local culture: what they can tell about the actual soldiers. In the wake of the context theories highlighting the importance of not only the folklore text, but also its social existence, the focus of analysis is on the storytellers and their environment. The research comprises both the published folktale texts and their manuscript variants preserved at the Lithuanian Folklore Archives of the Institute of Lithuanian Literature and Folklore. Mainly, the folklore materials recorded from the second half of the 19th to the beginning of the 20th century are analyzed; however, lack of the contextual information requires using the data from the second half of the 20th century as well, since it enables more exhaustive discussing of the background of the narratives and the modes of their dissemination. Soldiers used to act as certain mediators for the folktales from faraway lands to reach the Lithuanian territory. Their active life style facilitated both acquisition of the new texts and their dissemination. Having travelled far from home in order to carry out military service, the soldier communicated with his brothers in arms, acquiring new narrative experiences. Having returned home, he started recounting the stories learned abroad, thus transferring the new knowledge, experiences, and entire folktales or their motives. In case of soldiers, the storytelling comprised certain form of amusement, the mode of communication or even means of enhancing their social status. Such folktales bear clear traces of historical realities. Folktales recorded during different periods mention various military ranks of the tsarist Russian army. The soldier in the folktales usually is the central figure replacing other typical folktale characters – strongmen and valiant heroes. His adventures end up in a typical way: having successfully performed a difficult task the soldier is duly rewarded. Such folktales can acquire traits of a biographical narrative, since the storyteller has experienced the soldier’s life himself and is likely to include his own experiences into the narrative. In some cases, such folktales enriched with elements of the soldiers’ life grew well established in the local tradition, circulating around for a considerable time. Therefore, some pieces have been recorded not from the soldiers. The oldest details of the soldiers’ life found in the folktales reach back as early as the beginning of the 19th century. Usually, the recounted past events are supposed to comprise the storyteller’s lifetime. However, folktales recorded in the second half of the 19th century or even in the second half of the 20th century, and containing certain elements of the soldier’s life are likely to reflect centuries-old realities. The prolonged forced removal from home, experienced by the soldier is established as an introductory formula of the tale, depicting the soldier’s travel after the many years of service. Thus, the initial impulse related to the tiresome military service acquired as early as the beginning of the 19th century, was strong enough to persist in the folk memory for over a hundred years. This is one more evidence to the folktales’ higher resistance to their surroundings: these narratives not only preserve the structural framework of the story, but also the details that had lost their historical relevance many years ago, transforming themselves subsequently into established components of the narrative that bear mainly esthetical value.